Study on Mechanical Features of Brazilian Splitting Fatigue Tests of Salt Rock - Weichao Wang; Mengmeng Wang; Xiliang Liu (Advances in Civil Engineering)
The microtest, SEM, was carried out to study the fracture surface of salt rock after the Brazilian splitting test and splitting fatigue test were carried out with a servo-controlled test machine RMT-150B. The results indicate that the deviation of using the tablet splitting method is larger than that of using steel wire splitting method, in Brazilian splitting test of salt rock, when the conventional data processing method is adopted. There are similar deformation features in both the conventional splitting tests and uniaxial compression tests. The stress-strain curves include compaction, elasticity, yielding, and failure stage. Both the vertical deformation and horizontal deformation of splitting fatigue tests under constant average loading can be divided into three stages of “loosening-tightness-loosening.” The failure modes of splitting fatigue tests under the variational average loading are not controlled by the fracturing process curve of the conventional splitting tests. The deformation extent of fatigue tests under variational average loading is even greater than that of conventional splitting test. The tensile strength of salt rock has a relationship with crystallization conditions. Tensile strength of thick crystal salt rock is lower than the bonded strength of fine-grain crystals.